(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2016)
This compositional project deals with the creation of a musical work for single flute based on trajectories in a Cartesian plane describing a spiral. The proposed composition procedures have a quantitative approximation based on an algorithmic type model. The compositional process is given by a set of mathematical operations where finally the sound fact serves to translate an abstract structure to the real space-time and to be able to perceive it auditively.